2012
DOI: 10.1167/iovs.12-10516
|View full text |Cite
|
Sign up to set email alerts
|

Toward an Animal Model of the Human Tear Film: Biochemical Comparison of the Mouse, Canine, Rabbit, and Human Meibomian Lipidomes

Abstract: Our side by side comparison of the rabbit and the human meibum demonstrated their vast differences. Thus, the rabbit seems to be a poor animal model of the human tear film, at least when studying its biochemistry and biophysics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
128
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(131 citation statements)
references
References 41 publications
3
128
0
Order By: Relevance
“…The results of the HPLC-MS and other analyses of these normal samples already have been reported recently. 25,26 The analyses demonstrated a low intersample variability of the meibomian lipids among healthy, non-dry eye subjects. The lipid composition of meibum samples analyzed in our current study was shown to match the average lipid composition of meibum reported previously.…”
Section: Collection Of Meibum Samplesmentioning
confidence: 87%
See 1 more Smart Citation
“…The results of the HPLC-MS and other analyses of these normal samples already have been reported recently. 25,26 The analyses demonstrated a low intersample variability of the meibomian lipids among healthy, non-dry eye subjects. The lipid composition of meibum samples analyzed in our current study was shown to match the average lipid composition of meibum reported previously.…”
Section: Collection Of Meibum Samplesmentioning
confidence: 87%
“…The lipid composition of meibum samples analyzed in our current study was shown to match the average lipid composition of meibum reported previously. 17,[24][25][26][27][28] The biophysical experiments with fresh samples were conducted within a few days of collection. Bovine brain Cer and FC (>99% pure) were purchased from Sigma-Aldrich Corp.…”
Section: Collection Of Meibum Samplesmentioning
confidence: 99%
“…It is worthwhile noting that to analyse the lipids in meibum and in tears (see below) is extraordinarily difficult because of small sample sizes, ease of contamination, biological variation, major differences in lipid classes (each class needs different separation and analysis techniques), lack of standards, and the plethora of individual lipid species within a single sample (something only truly appreciated by those attempting the analysis). Overlayed on this complexity has been a confusion generated because on some occasions contaminants from plastics or solvents have been attributed to meibum (Butovich, 2009a;Nichols et al, 2007), and because the composition of rabbit meibum (used as an animal model) appears to be markedly different from that of other animals including humans (Butovich et al, 2012). It is therefore unsurprising that the analysis of the lipids has been a topsy-turvy ride with considerable variation in the data.…”
Section: Composition Of Meibummentioning
confidence: 99%
“…Owing to anatomical similarities, mice are a popular model for studying the pathogenesis of MGD. Furthermore, mouse meibum lipid composition strongly resembles that of humans (Butovich et al, 2012) and mouse Meibomian glands show an age-related atrophy that mimics changes seen in age-related MGD (Jester et al, 2011). MGD has been studied in mice exposed to a desiccating environment (Suhalim et al, 2014) or in diverse genetically modified mice lacking enzymes or transcription factors important for sebaceous lipid synthesis (House et al, 2010;McMahon et al, 2014;Yagyu et al, 2000).…”
Section: Discussionmentioning
confidence: 99%